In Vivo Analysis of the Role of atTic20 in Protein Import into Chloroplasts - Chen, Xuejun (American Society of Plant Biologists, 2002)
The import of nucleus-encoded preproteins into plastids requires the coordinated activities of membrane protein complexes that facilitate the translocation of polypeptides across the envelope double membrane. Tic20 was identified previously as a component of the import machinery of the inner envelope membrane by covalent cross-linking studies with trapped preprotein import intermediates. To investigate the role of Tic20 in preprotein import, we altered the expression of the Arabidopsis Tic20 ortholog (atTic20) by antisense expression. Several antisense lines exhibited pronounced chloroplast defects exemplified by pale leaves, reduced accumulation of plastid proteins, and significant growth defects. The severity of the phenotypes correlated directly with the reduction in levels of atTic20 expression. In vitro import studies with plastids isolated from control and antisense plants indicated that the antisense plastids are defective specifically in protein translocation across the inner envelope membrane. These data suggest that Tic20 functions as a component of the protein-conducting channel at the inner envelope membrane.